Analisis Pengaruh Citra Merek dan Norma Subjektif Terhadap Niat Kunjungan Ulang di Nasi Peda Pelangi Jakarta - Damara, Davy (TEHBMJ (Tourism Economics Hospitality and Business Management Journal), 2025)
This study aims to analyze the influence of brand image and subjective norms on customers' revisit intention to Nasi Peda Pelangi restaurant in Jakarta. The research is grounded in the argument that customer loyalty to sustainable restaurants can be strengthened by understanding the factors that influence it.